Effects of media exposure on PTSD symptoms in college students during the COVID-19 outbreak - Zhu, Xiao-Li; Wen, Zhu; Yu, Wen-Bo (Frontiers in Public Health, 2023)
Objective We aimed to investigate the influence of media on college students’ mental health during the COVID-19 pandemic. Methods After the COVID-19 outbreak, we used cross-sectional surveys through online questionnaires to investigate the mental health of college students in lockdown at home. We identified the influencing factors of PTSD symptoms using the Chi-Square test and ordinal logistic regression analysis. Results In 10,989 valid questionnaires, 9,906 college students with no PTSD symptoms, 947 college students with subclinical PTSD symptoms (1–3 items), and 136 college students with four or more PTSD symptoms were screened out. The results showed that media content impacted the mental health of college students in lockdown at home. Positive media content was negatively correlated with PTSD symptoms among college students. PTSD symptoms were not associated with sources of information. Moreover, College students with PTSD symptoms would reduce their willingness to learn and could not complete online learning efficiently. Conclusion PTSD symptoms are related to media exposure and excessive information involvement of COVID-19 in college students, which influences the willingness to attend online classes.